Assembly and performance of a 6.4 T cryogen‐free dynamic nuclear polarization system. (21st June 2017) - Kiswandhi, Andhika; Niedbalski, Peter; Parish, Christopher; Wang, Qing; Lumata, Lloyd
Abstract : We report on the assembly and performance evaluation of a 180‐GHz/6.4 T dynamic nuclear polarization (DNP) system based on a cryogen‐free superconducting magnet. The DNP system utilizes a variable‐field superconducting magnet that can be ramped up to 9 T and equipped with cryocoolers that can cool the sample space with the DNP assembly down to 1.8 K via the Joule–Thomson effect. A homebuilt DNP probe insert with top‐tuned nuclear magnetic resonance coil and microwave port was incorporated into the sample space in which the effective sample temperature is approximately 1.9 K when a 180‐GHz microwave source is on during DNP operation. 13 C DNP of [1‐ 13 C] acetate samples doped with trityl OX063 and 4‐oxo‐TEMPO in this system have resulted in solid‐state 13 C polarization levels of 58 ± 3% and 18 ± 2%, respectively. The relatively high 13 C polarization levels achieved in this work have demonstrated that the use of a cryogen‐free superconducting magnet for 13 C DNP is feasible and in fact, relatively efficient—a major leap to offset the high cost of liquid helium consumption in DNP experiments. Abstract : 13 C polarization levels close to 60% were achieved using a 180‐GHz DNP system based on a cryogen‐free superconducting magnet.